Health professionals’ experiences of tuberculosis cohort audit in the North West of England: a qualitative study - Wallis, Selina K (BMJ Open, 2016)
OBJECTIVES: Tuberculosis cohort audit (TBCA) was introduced across the North West (NW) of England in 2012 as an ongoing, multidisciplinary, systematic case review process, designed to improve clinical and public health practice. TBCA has not previously been introduced across such a large and socioeconomically diverse area in England, nor has it undergone formal, qualitative evaluation. This study explored health professionals’ experiences of the process after 1515 cases had been reviewed. DESIGN: Qualitative study using semistructured interviews. Respondents were purposively sampled from 3 groups involved in the NW TBCA: (1) TB nurse specialists, (2) consultant physicians and (3) public health practitioners. Data from the 26 respondents were triangulated with further interviews with key informants from the TBCA Steering Group and through observation of TBCA meetings. ANALYSIS: Interview transcripts were analysed thematically using the framework approach. RESULTS: Participants described the evolution of a valuable ‘community of practice’ where interprofessional exchange of experience and ideas has led to enhanced mutual respect between different roles and a shared sense of purpose. This multidisciplinary, regional approach to TB cohort audit has promoted local and regional team working, exchange of good practices and local initiatives to improve care. There is strong ownership of the process from public health professionals, nurses and clinicians; all groups want it to continue. TBCA is regarded as a tool for quality improvement that improves patient safety. CONCLUSIONS: TBCA provides peer support and learning for management of a relatively rare, but important infectious disease through discussion in a no-blame atmosphere. It is seen as an effective quality improvement strategy which enhances TB care, control and patient safety. Continuing success will require increased engagement of consultant physicians and public health practitioners, a secure and ongoing funding stream and establishment of clear reporting mechanisms within the public health system.